Functioning of linear induction accelerator of electrons LIA-30 in the mode of simultaneous forming and acceleration of 2 - 3 high-current relativistic electron beams - Grishin, A.V.; Gritsina, V.P.; Gornostaj-Pol’ski, S.A.; Slyusarenko, S.Ya.; Tarasov, A.D.; Kul’gavchuk, V.V. (Вопросы атомной науки и техники, 2001)
The carried out experimental investigations of LIA-30 accelerator injection system as well as the new data on standard operation modes testing in bremsstrahlung pulse generation made it possible to take a new view of electrophysical processes taking place in the accelerating track. In spite of success achieved in searching for optimal acceleration conditions – namely, limitation of edge steepness and amplitude of injection current pulses, definition of the program of forming voltage pulses that accelerate electrons etc. – there still remains to acute the task of decreasing lateral oscillations of high-current relativistic electron beam along the track as a whole and especially in cathode-anode gap where the influence of longitudinal magnetic field irregularities is most evident. When the magnetic field is limited in the track what is related to technical potentialities, the oscillations decrease in the injection system equipped with a two-beam cathode. Moreover, this process of electron beam acceleration becomes more stable even under conditions of parameter changes in the accelerator subsystem operation.